The transformation of work - Vallas, Steven P. (Steven Peter), 1951- (Amsterdam ; New York : JAI, 2001)
Analysts are generally agreed - dramatic changes are unfolding in the character of work, managerial authority, and the employment relationship. However, there is little agreement as to precisely how such changes are reshaping people's working lives, the nature of their careers, and the distribution of opportunity among members of different classes, genders, and ethnic groups. Confronting these issues head on, this text focuses on a series of critical questions concerned with the restructuring of work under capitalism at the beginning of the 21st century. The papers collected here address a wide array of workplace settings, from traditional manufacturing settings to "knowledge work" in high tech and university contexts. The volume devotes attention to the impact of production concepts in various national settings, ranging from Germany to Mexico and Australia. Among other themes, the volume also examines the linkage between gender inequality and efforts to establish innovative, "flexible" forms of work organization.
A collection of 10 essays by scholars in the field.
Includes bibliographical references.
Description based on print version record.
Keywords: Industrial sociology; Industrial sociology -- Case studies; Sociology: work & labour; Working patterns & practices; Business & Economics -- Labor; Social Science -- Sociology -- General